GPS TEC Scintillations and TEC depletion as seen from Hetauda and NAST, Nepal for 2016 - Ghimire, Basu Dev; Chapagain, Narayan Prasad; Khadka, Balaram; Bidari, Gambhir; Bhatta, Karan; Thapa, Aditya Singh (BIBECHANA, 2021)
We analyzed Global positing System Total Electron Content (GPS-TEC) data of stations Hetauda (27.414 0N and 85.051 0E) and NAST (27.656 0N and 85.327 0E), Nepal which are a part of UNAVCO.We obtained the variation of rate of TEC index (ROTI) and S4 index throughout the year 2016 for the two stations involved for the 32 all the Pseudo-Random Noise (PRN) numbers barring PRN number 4 which was inactive throughout the year. We chooses two stations data which are almost 40 km in distance and correlated the value of ROTI index with ROTI index and S4 index with S4 index and found that the ROTI index of Hetauda is well correlated with ROTI index of NAST with the highest being 94% for PRN 10 and the lowest being -13% for PRN 1. An extremely low correlation between S4 index of Hetauda and S4 index of NAST was observed with the highest correlation being 8% in PRN 3, 32 and the lowest correlation of -15% in PRN 12. BIBECHANA 18 (2) (2021) 87-94